Informational and Performance Properties of a Class of Iterative Planning Procedures - Clark, S. (Review of Economic Studies, 1984)
This paper analyses a class of iterative planning procedures that can be applied in environments describable by the Leontief-Samuelson technology. Members of the class are distinguished by the extent of the communication of technical information from firms to the Centre. All members of the class are monotonic and convergent, but the speed and finiteness of convergence is shown to depend critically on the extent of the transfer of technical information throughout each procedure. The paper thus establishes a trade-off between the informational and performance properties of a class of resource allocation mechanisms, taking environmental coverage as given.